Chemerin is associated with inflammatory markers and metabolic syndrome phenotypes in hypertension patients. (August 2014) - Gu, Ping; Jiang, Weimin; Lu, Bin; Shi, Zhaorong
Abstract Background: Chemerin is a new adipokine elevated in states of obesity and metabolic syndrome. In order to identify the role of chemerin in hypertension, we conducted a case--control study to evaluate the role of chemerin in hypertension. Methods: Two hundred and thirty-seven new-diagnosed essential hypertensive (EH) patients and one hundred and ten normotensive healthy subjects (NT) were enrolled. After an overnight fasting, participants underwent an oral glucose-tolerance test (OGTT). Anthropometric measurements and serum analyses were checked, including body mass index (BMI), waist circumference, insulin, triglycerides, total cholesterol, HDL-cholesterol, LDL-cholesterol, glucose, chemerin, hs-CRP, TNF-α and IL-6. Results: Compared with healthy controls, subjects with hypertension had significantly higher chemerin serum levels (p < 0.001). In hypertensive patients, chemerin level was significantly associated with metabolic characteristics including BMI, systolic blood pressure, fasting glucose and insulin, OGTT 2-hour glucose, plasma triglycerides, plasma total cholesterol, HOMA-IR and markers of inflammation including hs-CRP, TNF-α and IL-6, independent of age and gender. Only gender, HOMA-IR, TNF-α and TG were independently related factors to plasma chemerin level after multiple regression analysis. In logistic regression analysis, high chemerin level was an independent predictor of the presence of hypertension (OR: 1.045, p < 0.001) when metabolic variables were adjusted for. However, the association was lost when further adjustment for inflammatory markers including hs-CRP, TNF-α and IL-6 (OR: 1.022, p = 0.289). Conclusions: Chemerin is strongly associated with markers of inflammation and components of the metabolic syndrome in hypertensive subjects and was independently associated with hypertension after adjustment for age, gender and metabolic risk factors.